2015
DOI: 10.1139/cjfas-2013-0450
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and performance of wild and domestic strains of diploid and triploid rainbow trout (Oncorhynchus mykiss) in response to environmental challenges

Abstract: Physiology and performance of wild and domestic strains of diploid and triploid rainbow trout 1 (Oncorhynchus mykiss) in response to environmental challenges 2 3 by 4Abstract 11To determine the factors that may contribute to the poor survival of triploid (3n) rainbow trout 12 (Oncorhynchus mykiss) in lake stocking programs, we compared the physiology and responses to 13 environmental challenges of four wild strains and one domestic strain of diploid (2n) and 3n juvenile 14 rainbow trout. Over four successive y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 49 publications
0
39
2
Order By: Relevance
“…The results of the present study clearly demonstrate intraspecific variation in trueM˙O 2max , AAS, FAS, EPOC, O 2crit , ILOS and CT max among three strains of O. mykiss . In contrast, the majority of the previous studies that have independently examined variation in metabolic traits, hypoxia tolerance or upper thermal tolerance among strains of O. mykiss have found little evidence of intraspecific variation (Bidgood & Berst, ; Myrick & Cech, ; Rodnick et al., ; Scott et al., ). For instance, Scott et al .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The results of the present study clearly demonstrate intraspecific variation in trueM˙O 2max , AAS, FAS, EPOC, O 2crit , ILOS and CT max among three strains of O. mykiss . In contrast, the majority of the previous studies that have independently examined variation in metabolic traits, hypoxia tolerance or upper thermal tolerance among strains of O. mykiss have found little evidence of intraspecific variation (Bidgood & Berst, ; Myrick & Cech, ; Rodnick et al., ; Scott et al., ). For instance, Scott et al .…”
Section: Discussionmentioning
confidence: 93%
“…Intraspecific differences in metabolic rate, aerobic scope, critical oxygen level, hypoxia tolerance and upper thermal tolerance are not novel observations in fish generally and several previous studies have assessed at least one of these traits in domestic or wild strains of O. mykiss from the U.S.A., Canada, Austria, Italy, Australia and Japan (Fry, ; Bidgood & Berst, ; Klar et al., ; Lee & Rinne, ; Wieser et al., ; Scarabello et al., ; Strange et al., ; Alsop & Wood, ; Currie et al., ; McGeer et al., ; Myrick & Cech, , ; Carline & Machung, ; Faust et al., ; Molony et al., ; Rodnick et al., ; Ineno et al., ; Galbreath et al., ; LeBlanc et al., ; Recsetar et al., ; Chen et al., ; Scott et al., ; Verhille et al., ). In particular, these studies have demonstrated substantial variation in upper thermal tolerance, hypoxia tolerance, routine trueM˙O 2 and trueM˙O 2max in O. mykiss , which could be indicative of a large amount of intraspecific variation in this species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). CT max has a smaller range between 27.5 and 30°C for indigenous strains in British Columbia, Canada, when acclimated at 10°C (Scott et al, 2014) and in California, USA Cech, 2000, 2005), and in recently established strains in Pennsylvania, USA (Carline and Machung, 2001). For related redband trout that have adapted to a desert environment (Rodnick et al, 2004), where summer water temperature can oscillate from 18 to 30°C daily, CT max (29.7±0.3°C) was close to the upper daily water temperature recorded for those streams.…”
Section: Ct Maxmentioning
confidence: 98%
“…This lake-stocking program uses trout from at least 6 different strains of which roughly half are stocked as triploids. Triploidy is a condition that is produced by hatcheries in an attempt to induce sterility and promote growth, but triploid fish tend to be more sensitive to environmental challenge (Ojolick et al, 1995;Cotter et al, 2002;Scott et al, 2014). The increasing pH in many of BC lakes, particularly popular fishing lakes such as Green Lake, which has already reached a pH of~9.3, is of great concern for fisheries biologists and puts continued stocking efforts in jeopardy.…”
Section: Introductionmentioning
confidence: 99%